Writing Our Identities for Successful Endeavors: Resettled Refugee Youth Look to the Future. Issue 1 (2nd January 2019) - Daniel, Shannon M.
ABSTRACT: This article highlights recently resettled refugee teenagers' visions for their futures and their aims to improve the lives of their loved ones and transform society. Data collected in an afterschool writing workshop called Writing Our Identities for Successful Endeavors was analyzed using temporal facets of agency as a main lens to examine identity. Teenagers' written essays and their discussions about their futures show that they believe in their capabilities and choose a wide variety of career paths in order to improve the world. Attention to youth goals provides an important facet of identity beyond their past experiences. Too often, an overemphasis on refugees' pasts can position them as victims who need help. This article pushes back against essentialized, sometimes deficit, views of resettled refugees by focusing on their career aspirations and why they chose these goals. Implications for educators and researchers are discussed.